Behavioural response to heat ameliorative measures on buffalo heifers - VIJAYAKUMAR, P; PANDEY, H N; SINGH, MUKESH; DUTT, TRIVENI; S TOMAR, A K (The Indian Journal of Animal Sciences, 2011)
The present investigations were made to study the effect of heat ameliorative measures on the behavioural responses of buffalo heifers. Murrah buffalo heifers (18) between 15 and 30 months of age were divided into 3 equal groups based on body weight, viz. T1, control; T2, provided with only fan; and T3, provided with fan and sprinkling for 10 min at 2h intervals. Animals in T3 groups spent more time on rumination (35.24%) followed by T2 (31.04%) and T1 (30.23%). Similarly, animals in T2 group spent 28.75% of their time on feeding followed by T3 (26.35%) and T1 (22.04%) over a period of 24 h. Among the major behavioural patterns and postural parameters, only moving time showed significant difference among the groups. Also, watering and eliminative behaviours, viz. defecation and urination varied significantly among the groups. Among the various combined behavioural activities only standing feeding during night showed significant difference among the groups. In sitting posture, the impact of thermal stress on rumination during 24 h period differed significantly. The results from the present study indicated that only certain maintenance behavioural parameters differed significantly by provision of heat ameliorative measure on buffalo heifers.